Lin Yutang – filozof sztuki życia: Studium kluczowych zagadnień - Filipczuk, Magdalena (2023)
LIN YUTANG – A PHILOSOPHER OF THE ART OF LIFE: A STUDY OF KEY THEMESThe aim of this monograph is to present an interpretation of the works of Lin Yutang (1895-1976), a C hinese writer, thinker, translator, linguist, and inventor, from a philosophical perspective, with a special emphasis on the methods of contemporary comparative philosophy. Lin Yutang was, above all, a bilingual author and thinker, raised and educated simultaneously in two cultures, i.e. the Chinese tradition and the Christian culture of the English-speaking world. His immense erudition and intellectual ability naturally marked him out as an intermediary between the Chinese tradition and 20th-century Western civilization; in both a literal and a metaphorical sense, he translated the works of Chinese culture for the Western reader. In his long life, Lin published more than sixty books, forty of which came out in English; only six of these were novels. The list of his nonfiction pieces is much longer and includes, e.g. short and long essays, monographs on ancient Chinese sages, such as Confucius, Laozi or Zhuangzi, and their translations and anthologies. Lin gained particular popularity with several highly applauded fiction books and an effort to transplant Chinese culture to the West. After the publication of My Country My People (1935) and The Importance of Living (1937), he rose to great fame as a “Chinese philosopher,” but his philosophical thought, scattered throughout his many writings, has rarely been the subject of academic research.
Keywords: comparative philosophy; Chinese philosophy; philosophy of life; Chinese culture; contemporary philosophy